Optimization of Micro, Small, And Medium Enterprises (MSME) Through Business Digitalization Training (Finance and Marketing) - Sanjaya, Sonny; Marini, Sri; Saputra, Eka; Superwiratni, Superwiratni; Pramono, Fajar (Inaba of Community Services Journal, 2025)
Issues in economy are problems that are not escape from government talk. In The Strategic Plan (Ren-Stra) was initiated by Ministry Cooperatives and MSMEs 2019 empowerment 2024 explained Cooperatives and that MSMEs are mandate of law, one is the law. No. 20 of 2008 concerning Micro Business Conditions, these moments, On covid 19 period , almost all MSMEs in Indonesia caught impact Covid-19 pandemic . Even though MSMEs is one of the barometers from the economy national which means can increase economy in Indonesia. For this reason, MSMEs need existence support and encouragement from government especially so that the MSME actors can survive in conditions nowadays. Related to Cooperatives and MSMEs, government of west Java cares enough for development and empowerment . This Can seen from main thing that is regulation. As positive step, the government of the Bandung City in empowering Cooperatives and Businesses Small Medium , empowering MSMEs is integration from development economy expected national​ capable For improve and implement equality income as well as create field work. There is a need for education regarding the financial management and marketing of MSMEs. Akpar NHI Bandung provides training and workshops for the MSME community fostered by the Bandung City Industry Service to make the Micro Business mentoring program a success , in this case also involving students and lecturers in college tall For Can apply his knowledge For empowerment community. Through the micro and small business programs, through training finance, digital marketing, and assistance in obtaining Halal, PIRT, HAKI permits.